Taksu and Shackle of the Aesthetic Regimes in the Literation of Laksita Jati Music Yeni Amara - Joko Suranto; Rustopo Rustopo; Bambang Sunarto (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2020)
This article examines the problem of the literary composition of Laksita Jati music as a script for the final assignment of postgraduate students in the art creation program of the Institut Seni Indonesia (ISI) Surakarta. The focus of the study is centered on whether the final project text is part of the aesthetic practices of the co-operative aesthetic or adds weight to the music created? As intellectual property, the manuscript is one of the graduation conditions whose values are parallel to the work itself. With such importance, ideally, the music creation script should be able to describe the entire process until its production is comprehensive. In other words, this art creation script must be able to reflect the quality or weight of the work presented. However, if judging from the standardized system and format of writing, the text may be a fetter of creativity (cooperative regime) for creators who have a personal aesthetic orientation and vision. The assumption is that by referring to a systematic writing format often traps the writer to get absorbed in formalistic writing rules rather than writing the substance of his work itself. The author, in this case, is more concerned with the structure of writing than on content. Another argument is that if we look at the contents of the script, which is a reflection of overall performance, it is not impossible to be used to see the quality of music that students create. This study uses Bartes' synchronous and semiotic acceptance method,